Bioconversion of kitchen waste by Pichia kudriavzeii SGP1 (Sudhida Gautam Parihar1) - Sudhida G Parihar; Ram Dass Gautam (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The study was undertaken with a purpose of at source bioconversion of wet kitchen waste.  To accelerate the “Zero Waste Concept” and meet the UN’s Sustainable Development Goals 2015. Method: Wet waste was mixed with dry paper, cardboard material and a microbial culture was inoculated in the bag. Proper mixing of the material enhanced the process of composting. Results: Microgold-Y had a pH range of 6.7 to 7.0 with 45 to 58% moisture content, and suitable for plant growth. Germination test using radish (R. sativus) revealed 100% sprouting between 24 to 48 hrs on Microgold-Y (10%) followed with 93.3% on Microgold-Y (20%) as against 96.6 % in sand (control), grown in small containers (5x6 cm) at 20.2 to 20.7 0c and 58 to 65% RH.  Besides, profuse growth and flowering was observed in B. monnieri on Microgold Y while poor growth without flowering in control. Safety evaluation on earthworm, E. fetida revealed the survival of 60% as compared to 95% in control (cow dung). The worms produced undersized cocoons (<2mm) on microgold as compared to control (2.7 to 3.7 mm) and interestingly regained their reproduction on pre-mature microgold. Conclusion: The yeast was identified as Pichia kudriavzevii determined by the specialists at ICAR-Indian Agricultural Research Institute, New Delhi-12 based on NCBI Blast Result and FASTA Sequence.  The pH and moisture content of the product (Microgold-Y) ranged from 6.7 to 7.0 and moisture ranged from 45 to 58 per cent, which are ideal attributes of good compost recommended for field applications. Highlights: